Métodos de Autenticação em Segurança da Informação: redução de impactos em vazamento de dados. - ANUNCIAÇÃO, Elison Vinícius da Silva (2025)
Information security has become a priority for organizations due to the increasing number of data leakage incidents. This study explores the main authentication methods used to protect systems and data, highlighting their features, benefits, and limitations. Focusing on reducing the impacts of data breaches, the research analyzes traditional methods, such as passwords and PINs, as well as more robust solutions like multifactor authentication (MFA) and biometrics. The research too explores innovative solutions that minimize cybersecurity risks, contributing to a safer digital environment and equiped better. Through a literature review, trends and communication channels, best practices in the use of modern technologies to mitigate risks associated with sensitive information exposure are evaluated. The findings suggest that adopting more advanced methods can significantly reduce the impact of data breaches, ensuring better protection for organizations and their users.